Gravitational wave induced baryon acoustic oscillations - Döring, Christian; Centelles Chuliá, Salvador; Lindner, Manfred; Schäfer, Björn Malte; Bartelmann, Matthias (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 114 (2022) Gravitational wave induced baryon acoustic oscillations